2013
DOI: 10.1155/2013/754815
|View full text |Cite
|
Sign up to set email alerts
|

Body Fat and Breast Cancer Risk in Postmenopausal Women: A Longitudinal Study

Abstract: Associations between anthropometric indices of obesity and breast cancer risk may fail to capture the true relationship between excess body fat and risk. We used dual-energy-X-ray-absorptiometry- (DXA-) derived measures of body fat obtained in the Women's Health Initiative to examine the association between body fat and breast cancer risk; we compared these risk estimates with those for conventional anthropometric measurements. The study included 10,960 postmenopausal women aged 50–79 years at recruitment, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 49 publications
2
50
0
5
Order By: Relevance
“…The relation between body fat and BMI has been shown to vary by race/ethnicity (7072). Nevertheless, an analysis of the Women’s Health Initiative reported similar associations for measurement-based BMI and dual-energy-X-ray-absorptiometry (DXA) based body fat measures (73). We had to rely on waist and hip circumferences measured after diagnosis and had no data available on pre-diagnostic measures.…”
Section: Discussionmentioning
confidence: 97%
“…The relation between body fat and BMI has been shown to vary by race/ethnicity (7072). Nevertheless, an analysis of the Women’s Health Initiative reported similar associations for measurement-based BMI and dual-energy-X-ray-absorptiometry (DXA) based body fat measures (73). We had to rely on waist and hip circumferences measured after diagnosis and had no data available on pre-diagnostic measures.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, GPX3 directly targets the ERα gene in white adipose tissue, for which it was proposed as an important mediator of the estrogen effects in association with fat mass (42). Considering the link between visceral fat and breast cancer initiation and progression (43), it is reasonable to observe an overexpression of GPX3 in breast cancer cells. However, more specific studies are required to deeply understand the specific role of GPX3 in breast cancer.…”
Section: Rt-qpcr Evaluations On Human Breast Cancer and Non-cancerousmentioning
confidence: 99%
“…Unlike anthropometric measures, dual‐energy X‐ray absorptiometry (DXA) provides estimates of fat, bone, and bone‐free lean mass comparable to those from more costly methods such as computed tomography and magnetic resonance imaging . Using data from Women's Health Initiative (WHI), we have previously shown that various DXA‐derived measures of body fat were positively associated with risk of postmenopausal breast cancer . More recently, we also demonstrated that among normal BMI postmenopausal women, relatively high whole body fat and trunk fat (measured using DXA) were associated with almost twofold increases in risk of estrogen receptor‐positive (ER+) breast cancer …”
Section: Introductionmentioning
confidence: 99%